Cortical thickness in visuo-motor areas is related to motor outcomes after STN DBS for Parkinson's disease. (February 2020) - Frizon, Leonardo A.; Gopalakrishnan, Raghavan; Hogue, Olivia; Floden, Darlene; Nagel, Sean J.; Baker, Kenneth B.; Isolan, Gustavo R.; Stefani, Marco A.; Machado, Andre G.
Abstract: Introduction: Deep brain stimulation (DBS) is a widely accepted therapy for Parkinson's disease. While outcome predictors such as levodopa-response are well established, there remains a need for objective and unbiased predictors in clinical practice. We performed an exploratory study to examine whether cortical thickness, derived from preoperative MRI, correlates with postoperative outcome. Methods: Using freesurfer, we retrospectively measured cortical thickness on the preoperative MRI of 38 patients who underwent bilateral STN-DBS for PD during a 4-year period. The Unified Parkinson Disease Rating motor (UPDRS III) and experiences of daily living subscales (UPDRS II) were collected at baseline and six months after surgery. As an initial analysis, a series of partial correlations was conducted to evaluate the association between postoperative outcome scores and average cortical thickness from predefined regions of interest, adjusting for candidate confounders, without correcting for multiple comparisons. A confirmatory vertex-wise analysis was performed using a cluster-wise correction for multiple comparisons. Results: Based on the ROI analysis, the strongest correlation with motor outcome was found to be with the left lateral-occipital cortex. Patients with greater cortical thickness in this area presented with greater improvements in motor scores. This relationship was also supported by the vertex-wise analysis. Greater cortical thickness in frontal and temporal regions may be correlated with greater post-operative improvements in UPDRS II, but this was not confirmed in the vertex-wise analysis. Conclusions: Our data indicate that greater cortical thickness in visuo-motor areas is correlated with motor outcomes after DBS for PD. Further prospective investigations are needed to confirm our findings and better-investigate potential image biomarkers. Highlights: Cortical thickness in the left lateral-occipital cortex was correlated with post-operative motor outcomes. Outcomes in functional abilities were not related to cortical thickness in the same regions relevant for motor improvement. Motor outcomes after DBS may be dependent at least in part on motor imagery and planning based on visuo-motor interactions.